Costs and Scale-Up Costs of Integrating HIV Self-Testing Into Civil Society Organisation-Led Programmes for Key Populations in Côte d'Ivoire, Senegal, and Mali - d'Elbée, Marc; Traore, Métogara Mohamed; Badiane, Kéba; Vautier, Anthony; Simo Fotso, Arlette; Kabemba, Odé Kanku; Rouveau, Nicolas; Godfrey-Faussett, Peter; Maheu-Giroux, Mathieu; Boily, Marie-Claude; Medley, Graham Francis; Larmarange, Joseph; et al. (Frontiers in Public Health, 2021)
Despite significant progress on the proportion of individuals who know their HIV status in 2020, Côte d’Ivoire (76%), Senegal (78%), and Mali (48%) remain far below, and key populations (KP) including female sex workers (FSW), men who have sex with men (MSM), and people who use injectable drugs (PWuID) are the most vulnerable groups with a HIV prevalence at 5%-30%. HIV self-testing (HIVST), a process where a person collects his/her own specimen, performs an HIV test, and interprets the result, was introduced in 2019 as a new testing modality through the ATLAS project coordinated by the international partner organisation Solthis (IPO). In this paper, we estimate the costs of implementing HIVST through twenty-three civil society organisations (CSO)-led models for KP in Côte d’Ivoire (N=7), Senegal (N=11), and Mali (N=5). We modelled costs for programme transition (2021) and early scale-up (2022-2023). Between July 2019 and September 2020, a total of 51,028, 14,472 and 34,353 HIVST kits were distributed in Côte d’Ivoire, Senegal, and Mali, respectively. Across countries, 64%-80% of HIVST kits were distributed to FSW, 20%-31% to MSM, and 5%-8% to PWuID. Average costs per HIVST kit distributed ranged $12-$15 (FSW), $14-$27 (MSM), and $15-$143 (PWuID), driven by personnel costs at various intervention levels (53%-78% of total costs), and HIVST kits costs (2%-15%). Estimated average costs at scale-up ranged $6-$13 (FSW), $6-$23 (MSM), and $14-$50 (PWuID), and were mainly explained by the spreading of IPO costs over higher HIVST distribution volumes. In all three countries, CSO-led HIVST kit provision to KP showed relatively high costs during the study period related to the progressive integration of the programme to CSO activities and contextual challenges (COVID-19 pandemic, country safety concerns). The analysis of costs at scale suggests that, in the transition to scale-up and further integration of the HIVST programme into CSO existing activities, this model can evolve into an affordable HIV testing strategy. This is particularly relevant as it remains today the most promising strategy for reaching KP of the HIV epidemic, their sexual partners, and FSW clients not accessing HIV testing. Further research will assess the overall cost-effectiveness of this model.